1990
DOI: 10.1080/10601329008544810
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Characterization of A Maleic Acid Copolymer with An Inflexible Side Chain

Abstract: Viscometric, pH, optical, and calorimetric titration studies of an alternating copolymer of maleic acid and indene in aqueous NaCl of 0.01 to 0.27 Mat 15 to 35°C showed the conformational transition of a compact to an expanded coil upon ionization of the primary carboxyl groups. The thermodynamic parameters of the transition were calculated. The results indicate that the bulky and inflexible side chain in indene sterically interferes with the formation of the compact form of the copolymer, but stabilizes the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Unlike the PEO branched derivative the organoboron polymers exhibit typical polyelectrolyte behavior, i.e., increase in viscosity with a dilution of polymer water solution, which can be explained by specific behavior of complexed macromolecules and their conformational changes resulting in the expansion of polymer coil in the dilution solution. Similar effect was observed for the other carboxyl-containing polymers [27,28]. Thermal behavior and phase transitons of synthesized organoboron polymers were investigated by differential scanning calorimetric (DSC) and thermal gravimetrical analysis (TGA) methods.…”
Section: Functional Polymer Composition-property Relationshipsupporting
confidence: 57%
“…Unlike the PEO branched derivative the organoboron polymers exhibit typical polyelectrolyte behavior, i.e., increase in viscosity with a dilution of polymer water solution, which can be explained by specific behavior of complexed macromolecules and their conformational changes resulting in the expansion of polymer coil in the dilution solution. Similar effect was observed for the other carboxyl-containing polymers [27,28]. Thermal behavior and phase transitons of synthesized organoboron polymers were investigated by differential scanning calorimetric (DSC) and thermal gravimetrical analysis (TGA) methods.…”
Section: Functional Polymer Composition-property Relationshipsupporting
confidence: 57%
“…[18,19,34] The poly(MA-alt-a-olefin)s, as hydrophobic ethylenic copolymers, do not suffer conformation transitions in aqueous solution during the potentiometric titration. [35] This fact has been explained by the stabilization of the carboxylic polyacid compaction through hydrophobic intramolecular interaction between the nonpolar groups on the polymer chain.…”
Section: Polyelectrolyte and Swelling Behaviormentioning
confidence: 99%
“…Several characteristic properties have been studied, namely, the two-step dissociation of carboxylic groups [15] and binding of counterions, [16] pH-induced conformation transitions, [17] and a remarkable behavior of viscosity that exhibits a maximum at the half-neutralization point. [15,18] The synthesis and characterization of stimuli-responsive random copolymers of MA and N-isopropylacrylamide with different compositions (MA units in copolymers 20 mol-%) and their macromolecular reactions with poly(ethylene oxide) and poly(ethylene imine) have been reported as a route to obtain new reactive amphiphilic water-soluble polymers that are potentially useful as carriers for gene delivery. [19][20][21] It has been shown that synthesized copolymers with a given composition have a low critical solution temperature (LCST) in the range of 30.2-46.4 8C at pH values of 4.0-7.4, a fact that suggests the possibility of their use in biomedical applications, especially for enzyme immobilization to increase the thermal stability and activity of penicillin G acylase.…”
Section: Introductionmentioning
confidence: 99%
“…For the acidic form, the pyrene is located in hydrophobic zones but over a critical degree of neutralization, α N > 0.25, its environment becomes more hydrophilic. Such modifications were also observed for other copolymers of maleic acid with hydrophobic comonomers such as styrene, indene, or alkyl vinyl ethers connected with some discontinuity in the plot of p K function of ionization degree; 4a,, they were attributed to a conformational transition from a compact to an expanded coil upon ionization of the first carboxylic groups.
15 Plot of I 1 / I 3 ratio against α N for MAc−MMA.
…”
Section: Resultsmentioning
confidence: 58%